A network with nowhere to hide. Issue 10 (October 2021) - Kirk, Alex
Abstract : Supply chain compromises are at the top of every security professional's mind in the wake of the SolarWinds Sunburst breach. 1 The attackers behind that campaign were able to out-manoeuvre everything from point-in-time indicators of compromise (IOCs) to advanced heuristic algorithms, by thinking like a defender and crafting their malware to look like legitimate infrastructure.